Efficacy of the endoscopic rendez-vous technique for the reconstruction of complete esophageal disruptions - Gonzalez, Jean-Michel; Vanbiervliet, Geoffroy; Gasmi, Mohamed; Grimaud, Jean-Charles; Barthet, Marc (Endoscopy, 2016)
Background and study aims: The rendezvous endoscopic approach, already described, might be an interesting technique in complete esophageal obstructions (CEO).Patients and methods: This retrospective report on nine patients referred because of CEO classified patients into two groups based on length of their esophageal disruption: the long (> 5 cm) group were three patients (esophageal stripping at stent removal [n = 2] and caustic ingestion [n = 1]; two patients having superior esophageal sphincter [SES] destruction); the short (< 5 cm) group were six patients (anastomotic or post-radiotherapy). The procedures were performed under radiographic guidance. Results: All the reconstructions were successful. In four patients, a neo-SES was created, by transillumination (n = 2) or surgery (n = 2). The first dilation was performed by hydrostatic balloon, with additional metal stents (n = 4) and nasogastric tubes (n = 2) used. All the patients were able to eat after the procedure. Two delayed bleeds occurred, which were managed endoscopically. The patients underwent a median of seven dilations (range 3 – 55) over 8 months (2 – 32 months), with dilations ongoing in five patients, but all able to eat normally.Conclusion: Endoscopic rendezvous for CEO is safe and effective, even in patients with long disruptions and complete loss of SES.